Systematic Literature Review: Does Realistic Mathematics Education Approach Enhance Mathematical Literacy? - Paradesa, Retni; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Darmawijoyo, Darmawijoyo (Universitas PGRI Palembang, 2025)
Realistics Mathematics Education (RME) is an instructional approach that emphasizes the use of real-world problems and situations in mathematics teaching. This method is believed to significantly enhance students' mathematical literacy, which is crucial for their academic and everyday problem-solving skills. This systematic literature review aims to investigate the impact of RME on students' mathematical literacy by synthesizing existing research findings. A systematic review design was employed, focusing on studies that explore the relationship between RME and mathematical literacy. The Scopus database was utilized for bibliometric analysis, with the search term